Back Cover: Organic Molecular Layer with High Electrochemical Bistability: Synthesis, Structure, and Properties of a Dynamic Redox System with Lipoate Units for Binding to Au(111) (ChemPlusChem 7/2017). Issue 7 (14th June 2017) - Ohta, Eisuke; Uehara, Hiromitsu; Han, Ying; Wada, Kazuhisa; Noguchi, Hidenori; Katoono, Ryo; Ishigaki, Yusuke; Ikeda, Hiroshi; Uosaki, Kohei; Suzuki, Takanori
Abstract : The cover picture shows the first member of a dynamic redox system attached to a gold surface that can undergo electrochemical switching on the surface. Reversible C−C bond formation/cleavage upon two‐electron transfer endows the system with high electrochemical stability. This study demonstrates a prototype toward the realization of molecular‐based data storage devices using electrochemical input by a scanning tunneling microscopy tip. Details are given in the Communication by Takanori Suzuki and co‐workers onpage 1043 in Issue 7, 2017 (DOI:10.1002/cplu.201600649 ).